Boron Nitride Quantum Dots with Solvent‐Regulated Blue/Green Photoluminescence and Electrochemiluminescent Behavior for Versatile Applications. Issue 3 (27th December 2016) - Liu, Mengli; Xu, Yuanhong; Wang, Yao; Chen, Xu; Ji, Xuqiang; Niu, Fushuang; Song, Zhongqian; Liu, Jingquan
Abstract : Exploration of novel optical features, generation mechanisms, and versatile applicability of boron nitride quantum dots (BNQDs) is still in nascent stage. Herein, BNQDs are prepared using liquid exfoliation–solvothermal treatment of bulk BN in three different solvents. The photoluminescence of BNQDs is blue in ethanol (or N, N ‐dimethylformamide (DMF)) and green in N ‐methyl‐2‐pyrrolidone (NMP) under the same UV‐irradiation, respectively. The quantum yields (QYs) and average lateral sizes of the BNQDs are 12.6% and 4.1 ± 0.2 nm, 16.4%, and 2.8 ± 0.3 nm, as well as 21.3% and 2.0 ± 0.2 nm in solvents of ethanol, DMF, NMP, respectively. The distinct sizes, QYs, and optical properties of the BNQDs are found to depend on the polarity of these solvents. Different BNQDs can be chosen on‐demand for versatile applications. For example, the green BNQDs are much more competitive than the blue ones when serving as a fluorescent sensing platform for label‐free specific detection of ferric ions, while the blue ones in ethanol are much handier for cell imaging and fiber staining. More importantly, electrochemiluminescence (ECL) property of the BNQDs is observed and studied for the first time using cysteine as a co‐reactant. The possible ECL response mechanism of the BNQDs system is also proposed. Abstract : Boron nitride quantum dots (BNQDs) with solvent‐regulated blue/green photoluminescence and electrochemiluminescent behavior are prepared using liquid exfoliation–solvothermal treatment of bulk BN. The sizes, quantum yields, and optical properties of the BNQDs are varied with different polarity of the tested solvents. Different kinds of BNQDs can be chosen on‐demand for applications in label‐free specific ferric ion detection, cell imaging, and fiber staining.